Upaya Meningkatkan Kreativitas Matematis Siswa Sekolah Menengah Pertama Negeri 5 Terbuka Medan dengan Menggunakan Modul Model Learning cycle - Izwita Dewi; Siti Lisiani (Didaktik Matematika, 2015)
Abstract. This class room action research aimed to improve students' mathematical creativity in mathematical problem solving, and described the learning process of students of SMP Negeri 5 Terbuka. The learning method used module learning cycle models. This research was conducted in two cycles included the steps of planning, implementation of action, observation, and reflection. Students' mathematical creativity in solving mathematical problems measured was fluency, flexibility, elaboration, and originality. The results showed that students' mathematical creativity in mathematical problem solving increased. The aspects of the students' mathematical creativity in mathematical problem solving that most increased in this study were elaboration.Keywords: mathematical creativity, solving mathematical problems, module learning cycle models